Partisipan Wanita Dalam Olahraga Bulutangkis Kota Padang - Durrotun Salsabillah; Endang Sepdanius; Ahmad Chaeroni; Windo Wiria Dinata (Jurnal IKEOR, 2024)
Abstract: The problem in this study is the lack of female participants in badminton at the Padang City Badminton Hall Field. This study aims to determine female participants in badminton at the Padang City Badminton Hall Field. The design of this research is qualitative research with descriptive methods. The subject of this study was a woman in the Badminton hall of Padang City, with a sample of 15 people. The method of selecting informants uses the purposive sampling method. Data collection techniques are carried out by means of observation, interviews and documentation. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery, cameras and cellphones. The steps of analyzing data are data reduction, data presentation and drawing conclusions. The results showed that women’s participation at this time has increased quite well compared to before, this can be seen from the participation of women in badminton obtained through researchers’ interviews with speakers. On average, of the 13 female speakers who actively participate in badminton in a week, there is 1 woman with a frequency of playing time in a week 5 times. Then, the other 12 female speakers played badminton 2 times a week on average. One of the obstacles experienced by female speakers who play badminton is related to time constraints and the field where badminton is played.